Adenotonsilektomi pada Anak dengan Hidrosefalus - Syukrinto, Gustav; Amanda, Cindy Julia; Puspitasari, Ratih (PERHATI-KL, 2024)
Background: Hydrocephalus is an expansion of the ventricular system resulting from the condition of the brain, with altered circulation of the cerebrospinal fluid. The expansion could lead to an increase in intracranial pressure (ICP). Some procedures in adenotonsillectomy also could increase ICP, and lead to brain injury. Purpose: To study complications in performing adenotonsillectomy procedures on a child with hydrocephalus. Case report: A 3-year-old girl presented with hydrocephalus with recurrent sore throat, runny nose, cough, and fever at least once a month for about one year. She also presented with a history of sleep disturbance, such as snoring, nocturnal awakening, often mouth breathing, and bedwetting. During an ear, nose, throat (ENT) examination, the tonsil size was T4/T4, with dilated crypts and no detritus. The nasendoscopy examination revealed that she had a grade III adenoid hypertrophy. Clinical question: What to consider in minimizing complications of adenotonsillectomy in children with hydrocephalus during and after the surgery? Method: A literature search was performed on PubMed and Google Scholar, with keywords “Adenotonsillectomy” AND “Hydrocephalus” AND “ Intracranial Pressure”. Result: Based on the search, some procedures were found, such as intubation, placing a mouth gag, and head positioning during operative surgery, could increase ICP. Conclusion: There are some considerations when performing adenotonsillectomy in children with hydrocephalus that should be carefully prepared, to prevent increased ICP and brain injury during and after surgery. Keywords: adenotonsillectomy, hydrocephalus, intracranial pressure, tonsil hypertrophy ABSTRAK Latar belakang: Hidrosefalus merupakan perluasan sistem ventrikel otak akibat gangguan sirkulasi cairan serebrospinal. Perluasan tersebut dapat menyebabkan peningkatan tekanan intrakranial (TIK). Beberapa prosedur pada adenotonsilektomi juga dapat meningkatkan TIK dan menyebabkan cedera otak. Tujuan: Untuk mengetahui komplikasi dalam melakukan tindakan adenotonsilektomi pada anak dengan hidrosefalus. Laporan kasus: Seorang anak perempuan berusia 3 tahun datang dengan hidrosefalus dan riwayat nyeri tenggorokan berulang disertai pilek, batuk, dan demam setidaknya sebulan sekali, selama kurang lebih satu tahun. Ia juga memiliki riwayat gangguan tidur, seperti mendengkur, terbangun di malam hari, sering bernapas melalui mulut, dan mengompol. Dari pemeriksaan Telinga, Hidung, Tenggorok (THT), didapati pembesaran tonsil ukuran T4/T4, dengan kriptus melebar dan tidak ada detritus. Dari pemeriksaan nasendoskopi, ditemukan hipertrofi adenoid derajat III. Pertanyaan klinis: Apa yang harus dipertimbangkan dalam meminimalkan komplikasi adenotonsilektomi pada anak dengan hidrosefalus, baik selama dan setelah operasi? Metode: Pencarian literatur dilakukan di PubMed dan Google Scholar, dengan kata kunci “Adenotonsilektomi” DAN “Hidrosefalus” DAN “Tekanan Intrakranial”. Hasil: Berdasarkan penelusuran, didapati beberapa prosedur, seperti intubasi, pemasangan mouth gag, dan posisi kepala selama operasi bedah, dapat meningkatkan TIK. Kesimpulan: Terdapat beberapa pertimbangan dalam melakukan adenotonsilektomi pada anak dengan hidrosefalus, yang sebaiknya dilakukan secara hati-hati untuk mencegah peningkatan TIK dan cedera otak, baik pada saat atau setelah melakukan operasi. Kata kunci: adenotonsilektomi, hidrosefalus, tekanan intrakranial, hipertrofi tonsil